Symptomatic bone marrow metastasis in triple-negative breast cancer: a case report and literature review - Zheng, Chenhui; Dai, Jingjing; Wang, Yu; Zheng, Danni; Lin, Renzhi; Zheng, Zhibao (Frontiers in Oncology, 2025)
Bone metastasis is common in breast cancer, but symptomatic bone marrow involvement is exceedingly rare. This report presents a case of a young female patient with triple-negative breast cancer (TNBC) initially presenting with symptomatic bone marrow metastasis. Upon admission, blood tests revealed severe thrombocytopenia. Bone marrow biopsy confirmed tumor cell infiltration, and immunohistochemistry identified metastatic breast cancer cells. The patient received paclitaxel and eribulin chemotherapy combined with transfusion support, achieving significant symptom control. This rare case highlights the importance of early detection and aggressive management in TNBC with bone marrow metastasis.